2002
DOI: 10.1097/00000478-200202000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Gynecologic Neoplasms in Patients With Proven or Suspected BRCA-1 or -2 Mutations

Abstract: Identification of inheritable mutations associated with the development of malignancy has led to prophylactic surgeries to remove tissues at risk. We report seven unrelated patients with family histories of breast and/or ovarian cancer, five of whom underwent prophylactic salpingo-oophorectomy with hysterectomy. Four had proven BRCA-1 or -2 mutations. Malignant cells were found unexpectedly in the peritoneal washings of two patients, leading to the discovery of early-stage fallopian tube carcinoma. After chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
42
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(42 citation statements)
references
References 28 publications
0
42
0
Order By: Relevance
“…37 Beginning in the late 1990s, investigators began identifying early serous carcinomas of the fallopian tube in prophylactic salpingo-oophorectomies from women with BRCA mutations (BRCA+). [38][39][40] This finding necessitated a shift in management with emphasis on removing both tubes and ovaries from these patients. Since then, early serous carcinoma has been diagnosed in the fallopian tubes from approximately 2% to 10% of BRCA+ patients undergoing prophylactic bilateral salpingo-oophorectomy (table 1).…”
Section: Lessons From the Brca Populationmentioning
confidence: 99%
“…37 Beginning in the late 1990s, investigators began identifying early serous carcinomas of the fallopian tube in prophylactic salpingo-oophorectomies from women with BRCA mutations (BRCA+). [38][39][40] This finding necessitated a shift in management with emphasis on removing both tubes and ovaries from these patients. Since then, early serous carcinoma has been diagnosed in the fallopian tubes from approximately 2% to 10% of BRCA+ patients undergoing prophylactic bilateral salpingo-oophorectomy (table 1).…”
Section: Lessons From the Brca Populationmentioning
confidence: 99%
“…[30][31][32][33][34] These findings have engendered speculation that 'ovarian' carcinomas in women with BRCA1 mutations may originate from undetected exfoliated tubal carcinomas 30,33,35 and have led to the suggestion that ovarian and fallopian tube carcinomas in women with BRCA mutations should be termed 'female adnexal carcinoma'. 24,35 …”
Section: Morphologic Datamentioning
confidence: 99%
“…The reasons include different histologic and immunophenotypes between ovarian surface epithelium and ovarian epithelial cancers, the pathologic properties of ovarian epithelial cancers showing striking similarities to Mullerian epithelia, 3 and the presence of precancerous lesions of ovarian high-grade serous carcinomas in tubal fimbria but not in the ovary or on ovarian surface. [4][5][6][7][8][9] All these findings, as well as other factors, have led to an increased recognition in recent years that the fallopian tube is the likely source of most pelvic high-grade serous carcinomas. 6,10 Recent molecular studies have suggested that ovarian epithelial cancers can be divided into two broad groups.…”
mentioning
confidence: 99%